Analysing THE Impact of Road Information System on Traffic Safety. (2017) - Török, Árpád; Pauer, Gábor; Berta, Tamás
Abstract: This paper provides a complex analysis framework for evaluating the role of appropriate transmission (appropriate quality, quantity, location and timing) of information in case of infrastructure safety and accident categories. The aim of the "infrastructure module" of the methodology is to evaluate, how much the appropriate transmission of information influences road safety at a given section of the road infrastructure. The aim of the "accident module" of the methodology is to define those types and causes of accidents, which are remarkably influenced by the appropriateness of information transmission.